2018
DOI: 10.1021/acs.inorgchem.7b02635
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability and Mechanisms of Transformation of La-Doped γ-Alumina

Abstract: We report the phase stability of cubic γ-AlO with respect to lanthanum dopant amount and describe a complete phase transition sequence up to a temperature of 1800 °C, which proceeds from La-doped γ-AlO to LaAlO/γ-AlO to LaAlO. For this purpose, lanthanum contents from 0.81 to 10.0 atom % were incorporated into AlO powders. X-ray diffraction analyses show that only γ-AlO phase was present after heat treatment at 1000 °C for 2 h with 0.81, 1.68, 2.24, and 2.62 atom % lanthanum concentrations. The phase stabiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…In general, when elements with larger radii are incorporated, the diffraction peaks shift to a lower angle. However, the diffraction peak may shift to a high angle due to lattice distortion and stress, which is also found in other oxides doped with rare-earth elements. , In the XRD pattern of La-Al 2 O 3 , some weak peaks (23.4, 33.4, 41.2, 47.9, 59.7, and 70.1°) belonging to LaAlO 3 (JCPDS 31-0022) emerge in addition to the dominant peak of alumina, deriving from the solid-phase reaction between alumina and La 3+ . , The weak single peak at 2θ = 29.1° could be due to the trace formation of La 2 O 3 (JCPDS 83-1345). The appearance of LaAlO 3 and La 2 O 3 may relate to the aggregation of random dispersed La atoms as seen in the STEM image.…”
Section: Resultsmentioning
confidence: 94%
“…In general, when elements with larger radii are incorporated, the diffraction peaks shift to a lower angle. However, the diffraction peak may shift to a high angle due to lattice distortion and stress, which is also found in other oxides doped with rare-earth elements. , In the XRD pattern of La-Al 2 O 3 , some weak peaks (23.4, 33.4, 41.2, 47.9, 59.7, and 70.1°) belonging to LaAlO 3 (JCPDS 31-0022) emerge in addition to the dominant peak of alumina, deriving from the solid-phase reaction between alumina and La 3+ . , The weak single peak at 2θ = 29.1° could be due to the trace formation of La 2 O 3 (JCPDS 83-1345). The appearance of LaAlO 3 and La 2 O 3 may relate to the aggregation of random dispersed La atoms as seen in the STEM image.…”
Section: Resultsmentioning
confidence: 94%
“…For the SA, since the mullitization totally changed the phase transforming route, the mullite and θ-Al 2 O 3 instead of α-Al 2 O 3 were observed at 1300 • C. The LA remained metastable alumina at 1200 • C and evolved to α-Al 2 O 3 and LaAl 11 O 18 at 1300 • C, which is typical in a La 2 O 3 -Al 2 O 3 system with small amount of lanthanum. 24 It suggested that there was a chemical reaction between the alumina and lanthanum oxide. Both the SA and LA generated new substances after calcination at 1300 • C; however, the lanthanum addition is not able to effectively restrain the formation of α-Al 2 O 3 at this temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike Si 4+ with a smaller ionic radius of 0.04 nm, 35 since the radius of La 3+ (0.103 nm) is nearly twice that of Al 3+ (0.054 nm), it has poor solubility in the alumina. 24 Therefore, too much La 3+ in the LA would lead to unexpected precipitation and sintering. That is to say, too much of La in alumina would conversely harm its thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…Alumina, also known as corundum [28], is a ceramic material widely used in various applications due to its excellent mechanical and physicochemical properties, such as high hardness, high wear resistance, low thermal conductivity, high corrosion resistance, high chemical and electrical resistance [24,28,29]. In most published papers, authors refer to the α-alumina (α-Al 2 O 3 ) phase simply as alumina (Al 2 O 3 ) or corundum.…”
Section: Aluminamentioning
confidence: 99%
“…Despite several efforts involving the use of alumina-based materials in bone repair devices, there are still debates about the effect of alumina on bioactivity and osseointegration. Alumina varies from the amorphous phase to α-alumina (the most thermodynamically stable crystalline phase), where other metastable crystalline forms are also possible (χ, η, δ, κ, θ, γ, ρ), which are commonly called transition aluminas [24]. They differ in surface features, notably topography, surface area, and reactivity.…”
Section: Introductionmentioning
confidence: 99%